Preparation of psoralen polymer-lipid hybrid nanoparticles and their reversal of multidrug resistance in MCF-7/ADR cells - Qingqing Huang; Tiange Cai; Qianwen Li; Yinghong Huang; Qian Liu; Bingyue Wang; Xi Xia; Qi Wang; John C. C. Whitney; Susan P. C. Cole; Yu Cai (Taylor & Francis Group, 2018)
Multidrug resistance (MDR) is the leading cause of failure for breast cancer in the clinic. Thus far, polymer-lipid hybrid nanoparticles (PLN) loaded chemotherapeutic agents has been used to overcome MDR in breast cancer. In this study, we prepared psoralen polymer-lipid hybrid nanoparticles (PSO-PLN) to reverse drug resistant MCF-7/ADR cells in vitro and in vivo. PSO-PLN was prepared by the emulsification evaporation-low temperature solidification method. The formulation, water solubility and bioavailability, particle size, zeta potential and entrapment efficiency, and in vitro release experiments were optimized in order to improve the activity of PSO to reverse MDR. Optimal formulation: soybean phospholipids 50 mg, poly(lactic-co-glycolic) acid (PLGA) 15 mg, PSO 3 mg, and Tween-80 1%. The PSO-PLN possessed a round appearance, uniform size, exhibited no adhesion. The average particle size was 93.59 ± 2.87 nm, the dispersion co-efficient was 0.249 ± 0.06, the zeta potential was 25.47 ± 2.84 mV. In vitro analyses revealed that PSO resistance index was 3.2, and PSO-PLN resistance index was 5.6, indicating that PSO-PLN versus MCF-7/ADR reversal effect was significant. Moreover, PSO-PLN is somewhat targeted to the liver, and has an antitumor effect in the xenograft model of drug-resistant MCF-7/ADR cells. In conclusion, PSO-PLN not only reverses MDR but also improves therapeutic efficiency by enhancing sustained release of PSO.